Pseudo Primary-2-Absorbing Submodules and Some Related Concepts - Abdulla, Omar A.; Mohammadali, Haibat K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Let  be a commutative ring with identity. The aim of this paper is introduce the notion of a pseudo primary-2-absorbing submodule as generalization of 2-absorbing submodule and a pseudo-2-absorbing submodules. A proper submodule  of an -module  is called pseudo primary-2-absorbing if whenever , for , , implies that either                  or  or . Many basic properties, examples and characterizations of these concepts are given. Furthermore, characterizations of pseudo primary-2-absorbing submodules in some classes of modules are introduced. Moreover, the behavior of a pseudo primary-2-absorbing submodule under -homomorphism is studied.